THRIVE Conceptual Framework and Study Protocol: A Community-Partnered Longitudinal Multi-Cohort Study to Promote Child and Youth Thriving, Health Equity, and Community Strength - Anna K. Ettinger; Doug Landsittel; Kaleab Z. Abebe; Jamil Bey; Val Chavis; Judith D. Navratil; Felicia Savage Friedman; Terence S. Dermody; Elizabeth Miller; the Pittsburgh Study Committee Co-Leads (Frontiers Media S.A., 2022)
BackgroundGiven the profound inequities in maternal and child health along racial, ethnic, and socioeconomic lines, strength-based, community-partnered research is required to foster thriving children, families, and communities, where thriving is defined as optimal development across physical, mental, cognitive, and social domains. The Pittsburgh Study (TPS) is a community-partnered, multi-cohort study designed to understand and promote child and youth thriving, build health equity, and strengthen communities by integrating community partners in study design, implementation, and dissemination. TPS launched the Tracking Health, Relationships, Identity, EnVironment, and Equity (THRIVE) Study to evaluate children's developmental stages and contexts from birth through completion of high school and to inform a child health data hub accessible to advocates, community members, educators, health professionals, and policymakers.Methods and AnalysisTPS is rooted in community-partnered participatory research (CPPR), health equity, antiracism, and developmental science. Using our community-informed conceptual framework of child thriving, the THRIVE Study will assess cross-cutting measures of place, environment, health service use, and other social determinants of health to provide longitudinal associations with developmentally appropriate child and youth thriving outcomes across participants in six cohorts spanning from pregnancy through adolescence (child ages 0-18 years). Data from electronic health records, school records, and health and human services use are integrated to assess biological and social influences of thriving. We will examine changes over time using paired t-tests and adjusted linear regression models for continuous thriving scores and McNemar tests and adjusted logistic regression models for categorical outcomes (thriving/not thriving). Data analyses will include mixed models with a random intercept (in combination with the previously-specified types of regression models) to account for within-subject correlation.DiscussionBy enhancing assessment of child and youth well-being, TPS will fill critical gaps in our understanding of the development of child and youth thriving over time and test strategies to support thriving in diverse communities and populations. Through CPPR and co-design, the study aims to improve child health inequities across multiple socioecological levels and developmental domains.